Consumers Intention to Purchase Furniture Product Online in Bali: Using Modified of Technology Acceptance Model (TAM) - Mahmud Budianto; Nyoman Sri Subawa (Jurnal Manajemen Bisnis Performa, 2022)
The purpose of this study was to determine consumer perceptions of purchasing furniture through an e-commerce platform. The technology acceptance modification was further developed to be proposed in investigating website quality, service perception, and product perception on consumer purchase intention of online furniture items. Trust here acts as a mediator to study its effect on consumer intentions. Meanwhile, the influence of website quality, service perception, and product perception were analyzed for the modified constructs of the technology acceptance model, namely perceived ease of use, and perceived usefulness. 130 respondents were surveyed and analyzed using the Smart PLS technique. The results show that product perception has a positive effect on perceived usefulness and trust. Then the perception of service only has a positive effect on perceptions of usability and perceived ease of use. Website quality also affects trustworthiness and perceived ease of use. Perceived ease of use also impacts perceived usefulness. Meanwhile, Attitude to use has a direct positive effect on perceived usefulness, perceived ease of use, and trust. And lastly, the intention to use is directly influenced by the attitude to use.